ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUTUSAN KONSUMEN DALAM PEMBELIAN BARANG ELEKTRONIK SECARA KREDIT PADA PT COLUMBUS MEGAH SENTRA SARANA CABANG BERAU - Warti Ratnasari (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) Sekolah Tinggi Ilmu Ekonomi (STIE) Pontianak, 2020)
This study aims to analyze the factors that influence consumer decisions to purchase electronic goods on credit at PT Columbus Megah Sentra Sarana, Berau Branch. The data collection method used a questionnaire distributed to consumers of PT Columbus Megah Sentra Sarana, Berau Branch, as many as 92 people who were selected using probability sampling method with simple random sampling technique. The analytical tools used are: validity test, reliability test, multiple linear regression analysis, coefficient of determination, t test and F test.The results of this study indicate that the factors that have a significant influence are cultural factors, social factors and personal factors. Meanwhile, psychological factors have no significant effect on consumer decisions in purchasing electronic goods on credit at PT Columbus Megah Sentra Sarana, Berau Branch. So that the hypothesis of point 1 can be partially accepted and partially rejected.The results of the F test show that cultural factors, social factors, personal factors and psychological factors simultaneously have a significant influence on consumer decisions in purchasing electronic goods on credit at PT Columbus Megah Sentra Sarana, Berau Branch, so the hypothesis point 2 can be accepted